Fæðuofnæmi og fæðuóþol Íslendinga á aldrinum 20-44 ára - Davíð Gíslason; Eyþór Björnsson; Þórarinn Gíslason (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: Symptoms related to the intake of certain food items are common. In most of these cases food allergy/intolerance can not be confirmed. In the Icelandic part of the European Community Respiratory Health Survey the prevalence of food-related symptoms was assessed among adult Icelanders. Material and methods: Three thousand and six hundred men and women, 20-44 years, were studied, among them 800 were randomly chosen for a more detailed investigation. Additionally, all those using asthma medication or having asthma symptoms were investigated. A questionnaire inquired about chest symptoms, symptoms related to food-intake and eating habits. In Iceland additional questions were asked concerning drug intolerance, urticaria, Quincke oedema, childhood eczema, migraine and psoriasis. All subjects underwent skin prick tests against 12 common allergens, spirometry and methacholine challenge. Specific IgE antibodies against five airborne allergens and six common food allergens were measured. Results: Among subjects with food-related symptoms, 68% reported complaints from the GI-tract, 22% had skin rash or pruritus, 15% severe headache, 11% breathlessness, 8% a running/stuffy nose and 4% fatique. Altogether 42 food items were considered likely causes of the reported symptoms. Twenty-two percent of the random sample had symptoms related to the intake of a particular food and 15% reported always having the same symptom after intake of this food. Women reported food-related symptoms somewhat more often that men (17% and 13% respectively (p=0.21)). In the random sample only 1.8% had antibodies to one or more of the foods measured. There was a significant relationship between food-related symptoms and reported migraine, urticaria and Quincke oedema and a particularily strong relationship with drug intolerance. Migraine, urticaria, Quincke oedema and drug intolerance were significantly more common among women (p<0.0001, ...